2015
DOI: 10.1002/adem.201400583
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Silver Addition on Critical Current Densities and Mechanical Properties in Bulk MgB2

Abstract: The present study focuses on the effects of Ag addition on the critical current density (J c ) and the mechanical performance of disk-shaped MgB 2 bulk superconductors. MgB 2 samples with varying Ag contents of 0, 2, 4, 6, 8, and 10 wt% were sintered at 775°C for 3 h in Ar atmosphere. The J c values were improved with Ag addition, in that the sample with 4 wt% Ag showed the highest J c value of 295 kA cm À2 at 20 K and self-field. The respective J c values of the same sample were 430, 360, and 238 kA cm À2 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…This is because the control of MgB 4 in situ formation is difficult and once formed, MgB 4 disturbs stoichiometry of MgB 2 matrix. A similar scenario was observed when we tried to create Ag–Mg pinning centers in situ . We had to optimize the excess Mg required for maximum performance.…”
Section: Introductionmentioning
confidence: 66%
“…This is because the control of MgB 4 in situ formation is difficult and once formed, MgB 4 disturbs stoichiometry of MgB 2 matrix. A similar scenario was observed when we tried to create Ag–Mg pinning centers in situ . We had to optimize the excess Mg required for maximum performance.…”
Section: Introductionmentioning
confidence: 66%
“…Similarly, improvements had reported that Ag doping significantly enhances MgB 2 formation rate in MgB 2 wires with enhanced properties [22]. On the other hand, these results indicate that Ag addition to MgB 2 can be one of the ways to improve not only mechanical properties [17,[21][22][23][24] but also flux pinning; the critical temperature remains almost unchanged. It is also positive that Ag does not react with MgB 2 and can help to reduce cracks density like in cuprates [25].…”
Section: Magnetization Experimentsmentioning
confidence: 75%
“…More recently, EDX analysis by TEM had lucidly confirmed that Ag enriched phase distributed in MgB 2 matrix obtains a composition in close to AgMg 3 [21] and its size and dispersion in MgB 2 matrix is somewhat dependent on initially added silver content. Further, it was also confirmed by AFM observations that nanometer sized AgMg 3 particles were dispersed in MgB 2 matrix [17]. Therefore, it is essential to estimate the flux pinning behavior of bulk MgB 2 material with Ag addition and more details are presented below.…”
Section: Magnetization Experimentsmentioning
confidence: 77%
See 1 more Smart Citation
“…To improve the critical current density of the MgB2 material, a variety of processing techniques have been developed and studied in terms of commercially usefulness [9,10]. On the other hand, to improve the critical current density of these materials a variety of dopants [11][12][13][14] were adopted and very successful results were observed, especially using carbon-based dopants, e.g., carbon, boron carbide, carbon nanotubes, carbohydrates or hydrocarbons, graphene oxide, carbon-coated boron powders, etc. [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%